PENGARUH MODAL KERJA DAN PERTUMBUHAN PENJUALAN TERHADAP PROFITABILITAS PERUSAHAAN FOOD AND BEVERAGES YANG TERDAFTARDI BURSA EFEK INDONESIA - Andres Putranta Sitepu; Erieska Putri (Journal of Innovation Research and Knowledge, 2023)
This research aims to find out the effect of working capital, liquidity, and sales growth on the profitability in Food and Beverages companies which were listed on Indonesia stock exchange. The research was quantitative, while, the population was Food and Beverages companies which were listed on Indonesia stock exchange 2019-2021, moreover, the sampling collection technique used purposive sampling. In line with, there were ten companies as sample. Furthermore, the data analysis technique used multiple linier regression with SPSS version 20, as the hypothesis testing instrument. The research result concluded the working capital had negative and insignificant effect on the profitability of Food and Beverages companies which were listed on Indonesia stock exchange with significant 0,728. On the other hand, liquidity has positive and significant effect on the profitability of Food and Beverages companies which were listed on Indonesia stock exchange with significant 0,000. In addition, the sales growth had positive but insignificant effect on the profitability of Food and Beverages companies which were listed on Indonesia stock exchange with significant 0,545.